Educational technology: Conceptions and challenges in teaching practice (Research, Society and Development, 2023)
Digital technologies are teaching resources that can contribute to the quality of teaching and learning in Brazilian schools. They allow access to information from different sources, quickly and efficiently, narrowing the time and space between students and knowledge. The objective of this research is to discuss the concepts of educational technology and explain some challenges in its use in teaching practice. Education in the 21st century must accompany the process of changes that society demands as a contribution to the formation of concepts and values. We must be aware of a critical reading of the diverse reality, knowing, reflecting and acting in the face of conceptual differences and different types of technological resources. However, the work is a qualitative, descriptive and reflexive study. However, incorporating new technologies into the teaching and learning process is a challenge for teachers in the classroom, at the same time that their potential must be the subject of research and discussion in training courses. It is necessary to start from a critical analysis of the problem of education, and put educational technology at the service of the authentic purposes of education in social and cultural terms. Currently, man lives and coexists with technology and learns from information in the same dimension as its use.